A representação da mulher no sistema jurídico penal: um estudo de caso a partir das análises das expressões referenciais - Canuto, Sheyla; Colares, Virgínia (Language and Law / Linguagem e Direito, 2017)
The aim of this article is to identify through Critical Legal Discourse Analysis (ACDJ) textual references that may show evidence of the modes of operation of ideology regarding rst-instance judicial decisions in rape cases. The main question of this study is: what stereotype of women has been built by magistrates in their fundamental discourse about whether a rape occurred or not. Our hypothesis is that in cases of rape of women the discourse is usually focused on the victim’s behavior and not on the conduct of the accused. This research shows that judgments are not neutral. Rather, they are full of preconceptions and assumptions which can be identified by textual references reflecting particular linguistic choices. Last, but not least, this case study will help us understand the role of linguistic mechanisms in the architecture of sexist discourses in the Criminal Justice System.